Identification and Prevalence of Ixodid Ticks of Cattle in case of Haramaya Eastern Hararghe, Ethiopia - Anteneh Wondimu; Yehualashet Bayu (Veterinary Medicine International)
A cross-sectional study was conducted from December 2017 to April 2018 to determine the prevalence and identify major species of ixodid ticks of cattle and tick burden of different sex, age, breed, and body condition of cattle. Standard physical and direct stereomicroscopy techniques were employed for identification of tick species. During the study period, a total of 353 cattle were examined for presence of ticks and around 447 ticks were collected. The study showed that 34.3% cattle were infested with one or more tick species. The study reported different species of ticks in the order of their prevalence: A. variegatum (46.3%), Rh. decoloratus (20.1%), A. cohaerens (15.7%), A. gemma (11.9%), and Rh. pulchellus (6.04%), respectively. The prevalence of tick infestation between different risk factors such as sex, age, and body condition of cattle was statistically significant (p<0.05). The overall male-to-female ratio of ticks was 2.29 : 1. Also, it was reported that, in A. variegatum, A. cohaerens, and A. gemma, the number of male exceeded that of female, but female number exceeded male number in case of Rh. decoloratus. The result also reported difference in attachment site preference, for example, Amblyomma genus was attached mostly to the scrotum/udder and axial and Rh. pulchellus was specified on the ear and perianal area, while Rh. decoloratus was non site selective. In conclusion, findings of this study suggest that ticks were the most important problems of cattle of the study areas. Therefore, the increasing threat of ticks warrants urgent strategic control including application of acaricides and creation of awareness among livestock owners about the veterinary importance of ticks for the integrated tick control.